Perkembangan Kurikulum Pendidikan Agama Islam dan Pendidikan Budi Pekerti di SMA - Karlaely, Irma; Nugraha, Mulyawan Safwandy; Nursobah, Asep (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
The development of the Islamic Religious Education (PAI) and Character Education curriculum in Senior High Schools (SMA) is crucial amidst increasingly complex social dynamics. This research aims to analyze the curriculum development process of PAI and Character Education, focusing on the implementation of character-based learning methods. The research employs a qualitative approach through literature review to explore relevant theories and concepts. The research design centers on identifying curriculum development principles, including the stages of planning, implementation, and evaluation. The findings reveal that effective curriculum development involves intracurricular, co-curricular, and extracurricular activities, with the primary goal of shaping students with strong moral character and a deep understanding of religion. A holistic curriculum that is relevant to students' needs can strengthen their moral character and mitigate the negative influences from external environments. The implications of this research highlight the importance of collaboration between schools, parents, and the community in developing a PAI curriculum that can address contemporary challenges and prepare young generations to face modern life with integrity.